DNA damage response and anti-apoptotic proteins expression in NPMc+ mutated cells in acute myeloid leukaemia - Qutob, Haitham (2014)
Nucleophosmin 1 (NPM1) is a multi-functional phosphoprotein, which shuttles between the nucleolus and the cytoplasm. It participates in many cellular processes including ribosome biogenesis and transport, centrosome duplication, and also contributes to the control of genomic stability. NPM1 interacts with many proteins including those that participate in DNA damage repair processes. C-terminal mutations in NPM1 occur in 35% of patients with acute myeloid leukaemia and are associated with a good prognosis. They are characterised by delocalisation of NPM1 into the cytoplasm. This may have a role in the sensitivity of mutant cells to chemotherapy via inactivation of the DNA damage response processes.